New Antenna Array Architectures for Satellite Communications - Natera, Miguel Alejandro Salas; Aguilar, Andrés García; Cueva, Jonathan Mora; Fernández, José Manuel; Torre, Pablo Padilla De La; Trujillo, Javier García-Gasco; Rodríguez-Osorio, Ramón Martínez; Sierra-Perez, Manuel; Ariet, Leandro De Haro; Castañer, Manuel Sierra (IntechOpen, 2011)
None